The Implementation of the Principle of Profit Sharing of Mudharabah and Musyarakah in The Realm of Community Economic Development - Suherli, Ian Rakhmawan; Ridwan, Ahmad Hasan; Yusup, Deni Kamaludin; Hakim, Sofyan Al; Muharni, Yusraini (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
This study investigates the implementation of the profit-sharing concept through mudharabah and musharakah contracts within the context of community economic growth in general. Library research methods are utilized to collect and analyze relevant literature, emphasising how these two contracts might help Muslims avoid the usury trap. The study's findings reveal that mudharabah and musharakah have become an important feature of Indonesia's Islamic financial system, helping to finance productive enterprises. Although there are obstacles to its adoption, such as a lack of public comprehension and insufficient rules, both contracts have the potential to boost economic welfare significantly. This study also emphasizes the role of Islamic scholars and financial organizations in creating and overseeing this practice to ensure that Sharia principles are not breached